(untitled) (The Review of Diabetic Studies, 2025)
ST-elevation myocardial infarction (STEMI) remains one of the most time-critical cardiac emergencies, where every minute of delay increases myocardial damage and mortality. Paramedics play a vital role in reducing total ischemic time through early recognition, rapid activation of reperfusion pathways, and timely delivery of evidence-based prehospital interventions. This systematic review synthesizes current evidence on the impact of paramedic-led identification and management of STEMI in improving clinical outcomes. Database searches were conducted in PubMed, Scopus, Web of Science, and CINAHL (2016–2025), identifying studies evaluating prehospital ECG acquisition, STEMI diagnosis accuracy, prehospital activation of catheterization laboratories, early aspirin administration, and time-to-reperfusion metrics. Findings demonstrated that paramedic interpretation of 12-lead ECGs achieved diagnostic accuracy comparable to emergency physicians, significantly reducing door-to-balloon times. Prehospital cath-lab activation reduced treatment delays by 15–45 minutes across multiple systems. Early administration of antiplatelet therapy and optimized transport decisions further improved survival rates and reduced complications. The review concludes that paramedic-led early STEMI interventions are clinically effective and essential for high-performing emergency medical systems. Strengthening education, expanding ECG interpretation autonomy, and adopting tele-cardiology technologies are recommended to further enhance outcomes.